PRIMEIROS RESULTADOS POSITIVOS DE COMBATE Ã€ â€œSAÃšVA PARDAâ€ (Atta capiguara GONÃ‡ALVES, 1944) - Mariconi, Francisco A. M. (REVISTA DE AGRICULTURA, 2015)
PRIMEIROS RESULTADOS POSITIVOS DE COMBATE Ã€ â€œSAÃšVA PARDAâ€ (Atta capiguara GONÃ‡ALVES, 1944)